DIRECT FERTILIZER SUBSIDIES ON PRODUCTION AND HOUSEHOLD INCOME IN INDONESIA - Arrief Chandra Setiawan; Djoko Mursinto; Tri Haryanto (Faculty of Economics and Business, University of Pasundan, 2021)
This research aims to analyze the effect of fertilizer subsidies on the production and household income of rice farming in Indonesia using the 2017 crops business cost structure survey data. Utilizing the Ordinary Least Square (OLS) method, this research shows that rice farming households that received fertilizer subsidies have higher production and income than households that did not receive subsidies. Simultaneously, in the Two-Stage Least Square (TSLS) method, the usage of the ownership status of a household residential building as an instrument for the fertilizer subsidy variable is considered inaccurate so that it cannot answer the research objectives.